TIFAIFAI : Conception de Nouveaux Espaces d'Interactions pour Apprendre - Valérie Renault; Florent Carlier; Patrice Bourdon (Centre National d'Enseignement à Distance, 2014)
Contemporary education is more and more dependent upon computerized tools and technology delivery systems. These devices are often presented to teachers without specific modalities of educational activities or scenarios. Our main focus is to offer new interactive and mobile spaces designed to match the user's needs in context with both the teaching and learning experience. Our approach is based on a design methodology, initially conceptualized for general computational project management. The agile software development method SCRUM uses an empirical process control model incorporating the end user at each stage throughout the system design and development, including applicable experimental testing. We propose to adapt this method to the field of educational science in order to define and characterize new spaces in which educational interaction takes place. Taking end users into account throughout the entire designing process allows us to pin point new activities and opportunities related to unpredictable or imperfectly defined behaviors in teaching and learning. Within the frame of our objective, our project, TIFAIFAI, will be based on the implementation of configurable wall screens that interact with mobile systems.